Patients' satisfaction with hospital food provision at government hospitals in Malacca - Kamarudin, Nur Zakiah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Patients' hospital food consumption is often compromised, mainly because it is not reflective of their preferences and eating habits. This cross-sectional study was conducted to understand patients' satisfaction with various aspects of food provision in Malacca General, Jasin and Alor Gajah Hospitals. The Wesley Hospital Foodservice Patient Satisfaction Questionnaire (WHFPSQ) was adapted and used to collect the data throughout January and February 2015. Simple random sampling method was used to recruit 111 patients, aged 11-72 years, who received normal diet and had been admitted for ~1 day. Most of the patients were aged 30-39 years old (n=28, 25%), were male patients (n=69, 62%) and were hospitalised for 2-7 days (n=80, 72%).Majority were satisfied with hospital food (n=78 70.3%). In general, patients felt that not enough food choices were available and they were not able to choose healthy meals. Nevertheless, they felt staff who delivered their food were friendly, helpful and looked presentable. Food quality aspects (taste, flavour, method of vegetable cooked and expectation of quality of food), staff/service factors (staff behaviour, appearance and helpfulness) and portion size were significantly associated with overall satisfaction with hospital food (p<0.01). Physical environment, including odour (r=0.239) and noises (r=0.230) were also significantly associated with overall satisfaction with hospital food (p<0.05). Length of stay showed negative association (r=-0.338, p<0.01) with overall satisfaction, indicating that the longer they stay, the less satisfied they were with hospital food. However, no association was found between food choices, healthy meals, food texture and temperature with overall satisfaction. This study revealed that although overall satisfaction with hospital food was satisfactory, various factors including food and service elements affected patients' satisfaction. Satisfaction often reflects patients' actual food consumption. Therefore, findings of this study are useful in improvising provision of food, by taking into account the aspects that affected their satisfaction.